Quality of life in children with cochlear implants in Kazakhstan - Ruslan Zhumabayev; Galiya Zhumabayeva; Gulnara Kapanova; Nailya Tulepbekova; Anuar Akhmetzhan; Andrej Grjibovski (BMC, 2022)
Abstract Background Although cochlear implantation (CI) has been performed in Kazakhstan since 2007 little is known about quality of life of patients after CI. The aim of this study was to assess the health-related quality of life (HRQoL) of Kazakhstani children after CI. Methods Altogether, 53 families with a child using a cochlear implant for at least 1 year participated in the study between July 20, 2019 and February 20, 2020 at the Audiological Сenter of Almaty, Kazakhstan. The parents/caregivers completed the "Children with Cochlear Implants: Parental Perspectives (CCIPP)" questionnaire. Results 'Well-being and happiness' subdomain of the HRQoL yielded the highest ratings. 'Communication', 'general functioning', 'self-reliance', and 'supporting the child' subdomains each achieved significant (p < 0.01) associations with all HRQoL subdomains. There were positive correlations between language used by the parent who completed the questionnaire (Kazakh or Russian) and three HRQoL subdomains, including 'well-being and happiness', 'supporting the child' and 'social relations'. Conclusion Parents/caregivers reported high quality of life in all HRQoL subdomains. Further research in this area with more detailed socio-demographic and medical history data is required to identify quality of life predictors in children after cochlear implantation.